The Effect of Giving Different Feed Doses with the Addition of Viterna Plus Supplements on Fish Growth and Survival Rate Tambaqui (Colossoma macropomum) with Recirculation System - Ulfa, Fadilah Nur; Mulyadi, Mulyadi; Rusliadi, Rusliadi (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2025)
This research was carried out from April 2024 to June 2024 for 50 days. Maintenance is carried out at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Science, Universitas Riau. The aim of this research was to determine the effect of different feed doses added with viterna plus supplements on the growth and survival of tambaqui (Colossoma macropomum) using a recirculation system. The method used in this research is an experimental method using a one-factor completely randomized design (CRD) with 4 treatments and 3 replications. The treatments in this study were P1: Feed dose 3% of biomass weight, P2: Feed dose 5% of biomass weight, P3: Feed dose 7% of biomass weight, P4: Feed dose 9% of biomass weight. The best treatment is the P2 treatment (5%) which can increase absolute weight growth by 12.97±0.20, absolute length growth by 3.84± .18, specific growth rate by 3.55±0.00, efficiency feed was 63.56± 0.74, feed conversion ratio was 1.57 ± 0.02, and feed digestibility was 51.92%. The survival rate of tambaqui did not show any real influence and the best survival rate at P2 (5%) was 95%. Water quality parameters during the research found temperatures ranging from 26,3-27,6˚C, pH ranges from 6,7-7,0, DO ranges from 4,1-4,4 mg/l and ammonia ranges from 0,00144-0,00155 mg/L